Impact of Sensory Sensitivity on Physiological Stress Response and Novel Peer Interaction in Children with and without Autism Spectrum Disorder - Corbett, Blythe A.; Muscatello, Rachael A.; Blain, Scott D. (Frontiers in Neuroscience, 2016)
Background: For many children with Autism Spectrum Disorder (ASD), social interactions can be stressful. Previous research shows that youth with ASD exhibit greater physiological stress response during peer interaction, compared to typically developing (TD) peers. Heightened sensory sensitivity may contribute to maladaptive patterns of stress and anxiety. The current study investigated between-group differences in stress response to peer interaction, as well as the role of sensory sensitivity. Methods: Participants included 80 children (40 ASD) between 8-to-12 years. Children participated in the peer interaction paradigm (PIP), an ecologically valid protocol that simulates real-world social interaction. Salivary cortisol was collected before and after the 20 min PIP. Parents completed questionnaires pertaining to child stress (Stress Survey Schedule) and sensory sensitivity (Short Sensory Profile). Statistical analyses included t-tests and ANCOVA models to examine between-group differences in cortisol and play; Pearson correlations to determine relations between cortisol, play, and questionnaire scores; and moderation analyses to investigate interactions among variables. Results: Controlling for baseline cortisol values, children with ASD showed significantly higher cortisol levels than TD peers, in response to the PIP (F (1, 77) = 5.77, p = 0.02). Cortisol during play was negatively correlated with scores on the SSP (r = -0.242, p = 0.03), and positively correlated with SSS (r = 0.273, p = 0.02) indicating that higher cortisol was associated with greater sensory sensitivity (lower SSP reflects more impairment) and enhanced stress in various contexts (higher SSS reflects more stress). Furthermore, diagnosis was a significant moderator of the relation between cortisol and SSP, at multiple time points during the PIP (p < 0.05). Conclusions: The current study extends previous findings by showing that higher physiological arousal during play is associated with heightened sensory sensitivity and a pattern of increased stress in various contexts. Results are discussed in a broader context, emphasizing the need to examine relationships between social, behavioral, and physiological profiles in ASD to enhance understanding and improve treatments aimed at ameliorating stress and sensory dysfunction, while enhancing social skills.